Tari Baris Cina Sebagai Referensi Penciptaan Karya Seni Lukis - Divayana, I Putu; Yugus, A. A.; Kondra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
This Independent Project Report presents Chinese Baris Dance as a Reference for Painting Creation, departing from an interest in the visuals of Chinese Baris dance which is very unique and different from Baris dance in general. This sparked the impetus to present Chinese Baris dance visuals by combining certain references and techniques to achieve the desired meaning and purpose. The problem faced is how to visually process Baris Cina to represent the ideas and meanings that you want to realize to make it look attractive. The benefits and objectives of this report are to promote the existence of the Chinese Baris dance, and to increase the writer's understanding of the Chinese Baris dance. To answer the objectives of this work, the methods used are reflection or basic research, execution or forming, improvisation, and completion. With elements of art, and through the stages of reflection or basic research, execution or forming, improvisation, and completion, and combined with ideas and ideas to create 6 works entitled: 1) "Synergy", 2) "Bound" , 3) "authority", 4) "dexterity", 5) "taste", 6) "difference, blending, and balance". In the creation of the work, the author uses several techniques and references from several artists. By combining the object of smoke and the technique of using bamboo brushes and the tendency of romanticism, it is hoped that new works can be produced and can become the identity of the author. In the end, it can be concluded that the art of dance, especially the Chinese Baris dance, is very interesting to be promoted and gives a lot of inspiration that can be developed and will become a meaningful work. With the creation of this work, it is hoped that it can convey meaning or messages based on the aesthetic experience experienced by the author.